2012
DOI: 10.48550/arxiv.1205.3708
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extending the Concept of Probability Flux

Douglas J. Mason,
Mario F. Borunda,
Eric J. Heller

Abstract: We develop the Husimi map for visualizing quantum wavefunctions using coherent states as a measurement of the local phase space to produce a vector field related to the probability flux. Adapted from the Husimi projection, the Husimi map is complimentary to the usual flux map, since they are identical for small coherent states. By improving our understanding of the flux operator and offering a robust and flexible alternative, we show how the Husimi projection can provide a map to the classical dynamics underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Efforts, however, have been seen in the literature attempting to extend the standard concept of the probability current, e.g. by the group of E. J. Heller at Harvard University [52][53][54].…”
Section: B Some Critical Remarksmentioning
confidence: 99%
“…Efforts, however, have been seen in the literature attempting to extend the standard concept of the probability current, e.g. by the group of E. J. Heller at Harvard University [52][53][54].…”
Section: B Some Critical Remarksmentioning
confidence: 99%
“…Building off work in Husimi [2] and Mason et al [3], we define the Husimi function as a measurement between a wavefunction ψ ({r i }) and a coherent state |r 0 , k 0 , σ , which minimizes joint uncertainty in spatial and momentum coordinates. For lattice systems, the wavefunction represents the probability amplitude multiplier of localized wavefunctions indexed at discrete lattice sites, which are associated with discrete positions in the set {r i }.…”
Section: A Definition Of the Husimi Projectionmentioning
confidence: 99%
“…Earlier work has shown that for σk 1, Eq. 5 is proportional to the traditional flux vector expectation value [3]. For lattice systems, the traditional flux becomes a finite-difference approximation defined by the lattice.…”
Section: A Definition Of the Husimi Projectionmentioning
confidence: 99%
See 2 more Smart Citations

Husimi Maps in Lattices

Mason,
Borunda,
Heller
2012
Preprint
Self Cite